Cement properties effects to steel corrosion rate - Samsuri, Ariffin; K. S., Surej; M. A., Chandra; L. K., Yeoh; B., Suresh (1997)
Series of experiments were conducted in analysing the effect of fluid loss rate of cement slurry due to the existence of permeability contributing to the corrosion rate of cement slurry. Both class G and ordinary Portland cement (OPC) with different fluid loss were used to compare the cement protective effect on corrosion. The fluid loss was measured according to the API spec 10. 3.5% Natrium Chloride (NaCI) solution was used as the corrosion environment for reservoir and atmospheric conditions. A laboratory experiment is was done to study the influence of permeability for both types of cement. Permeability value was changed by alternating water cement ratio. Steel was put into cement mixture and left submerged in a brine solution. Submersion was done in atmospheric condition with a fixed temperature of 32oC and 52oC for reservoir condition. For both experiments, the A.C. Impendence technique was used. Results were discussed in depth to state that cement slurry with higher fluid loss will give a lower corrosion resistance, Rp and thus increasing the corrosion rate. Corrosion rate is higher at reservoir condition and both class G and OPC show the same characteristics and behaviour. However, class G cement shows better corrosion effective characteristic. Results from the permeability experiment shows that the permeability of OPC system is higher that the class G cement as well as the permeability being higher in reservoir condition rather than atmospheric condition.